ANALISIS STRATEGI GURU DALAM PELAKSANAAN PENGELOLAAN KELAS OLEH GURU KELAS V SD SWASTA ASSISI MEDAN - Antonius Remigius Abi; Lona Medita Lingga; Saut Mahulae; Syafri Fadillah Marpaung; Hambali Hambali (Jurnal Dedikasi Pendidikan, 2023)
The purpose of this research is to find out the teacher's strategy in implementing management class V in SD Private Assisi Medan. Type study descriptive qualitative. Technique collection data observation and interview. Results study that is strategy teacher in implementation management class Among other is teacher carry out organizing class with form organization class, list picket and class rules that have a goal so that the class is more organized and students have direction in the responsible answer on class. In arranging the place to sit down, the teacher places students according to the physical, psychological, and model conditions of learning that are applied in the classroom. Tools lessons are neatly arranged, the space class is maintained with good, clean, and comfortable, lighting enough, ventilation function, as well as Wall class gives color interesting for students.